A Qualitative Study Regarding the Leadership Traits and Styles of the Millennial Generation in the Manufacturing Industry - Thi Huynh Do, Nga; Van Nguyen, Phuong; Uyen Dinh, Phuong (International Journal of Engineering and Technology, 2018)
In human resource management, the motivations, expectations, strengths, and weaknesses of employees are important factors in an organization. For these factors, the Millennial is a generation that awaits higher expectations than previous generations. The current problems of leadership traits and styles are not well understood, especially businesses in Vietnam. This study deals with the behavior of the leaders in the place where they are working, Millennial take over the leadership role. The qualitative study aims to understand and explore the key characteristics and styles of Millennial leaders. Interest groups are affected by advanced technology, new perspectives on teamwork, professional requirements among peers, and their management. The topic is of particular interest to researchers as it transforms into a leadership role within the company. The data analysis showed good saturation and supported some key characteristics of Millennial when employees move in to reach out to their leaders. Companies can measure the success of a group through established accountability. For instance, a commitment to positive reinforcement as a primary motivation is the current widespread tendency.